2019
DOI: 10.1186/s13058-019-1206-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre- to postdiagnosis leisure-time physical activity and prognosis in postmenopausal breast cancer survivors

Abstract: BackgroundPhysical activity (PA) before and after breast cancer diagnosis has been reported to be associated with lower mortality. However, whether changes in the activity after diagnosis impact prognosis is unclear and has not received much attention. This study aimed to examine pre- to postdiagnosis leisure-time PA and breast cancer prognosis.MethodsWe used data from the MARIE study, a prospective population-based patient cohort study of 3813 postmenopausal breast cancer patients, aged 50–74 at diagnosis, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 23 publications
(45 reference statements)
4
44
1
Order By: Relevance
“…The review concluded that there is a need for randomized clinical trials (RCTs) investigating the role of physical activity on all-cause death and breast cancer outcomes. These results were further supported by recent evidence from the MARIE study, a population-based study of 3813 postmenopausal breast cancer patients [ 3 ]. Here, the authors showed that patients who are physically active have a better breast cancer prognosis than those who are inactive, especially for those who were not active before breast cancer diagnosis.…”
Section: Introductionsupporting
confidence: 79%
“…The review concluded that there is a need for randomized clinical trials (RCTs) investigating the role of physical activity on all-cause death and breast cancer outcomes. These results were further supported by recent evidence from the MARIE study, a population-based study of 3813 postmenopausal breast cancer patients [ 3 ]. Here, the authors showed that patients who are physically active have a better breast cancer prognosis than those who are inactive, especially for those who were not active before breast cancer diagnosis.…”
Section: Introductionsupporting
confidence: 79%
“…These results were further supported by recent evidence from the MARIE study, a population-based study of 3813 postmenopausal breast cancer patients [3]. Here the authors showed that patients who are physically active have a better breast cancer prognosis than those who are inactive, especially for those who were not active before breast cancer diagnosis.…”
Section: Introductionsupporting
confidence: 73%
“…Potentially eligible subjects were identified based on frequent monitoring of hospital admissions, surgery schedules, and pathology records of 51 clinics serving these regions and through the Hamburg Cancer Registry. In 2009, patients were re‐interviewed about weight and other exposures, and follow‐up information about endpoints was ascertained in 2009 and 2015 12 …”
Section: Methodsmentioning
confidence: 99%